2002
DOI: 10.1016/s1534-5807(02)00162-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of CREB Activity by the Rho GTPase Regulates Cell and Organism Size during Mouse Embryonic Development

Abstract: Rho GTPases regulate several aspects of tissue morphogenesis during animal development. We found that mice lacking the Rho-inhibitory protein, p190-B RhoGAP, are 30% reduced in size and exhibit developmental defects strikingly similar to those seen in mice lacking the CREB transcription factor. In p190-B RhoGAP-deficient mice, CREB phosphorylation is substantially reduced in embryonic tissues. Embryo-derived cells contain abnormally high levels of active Rho protein, are reduced in size, and exhibit defects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
134
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(143 citation statements)
references
References 44 publications
7
134
1
1
Order By: Relevance
“…It is also feasible that the induction of mDia in immune cells is related to the cell size increment in activated T cells and the corresponding growth of actin-based structures. In this regard, Rho has been involved in the regulation of cell size during embryonic development (37). Furthermore, activated T cells exhibit larger numbers of spontaneous lamellae and actin-rich tails than PBL (M. Vicente-Manzanares, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…It is also feasible that the induction of mDia in immune cells is related to the cell size increment in activated T cells and the corresponding growth of actin-based structures. In this regard, Rho has been involved in the regulation of cell size during embryonic development (37). Furthermore, activated T cells exhibit larger numbers of spontaneous lamellae and actin-rich tails than PBL (M. Vicente-Manzanares, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, those few studies commonly reported that the ablation of a specific GAP resulted in the global elevation of the activity of the target small GTPase (49,57,58); Rho GTP levels were highly elevated in P190B RhoGAP null murine embryonic fibroblasts (49), as was the Cdc42 GTP level in Cdc42GAP null murine embryonic fibroblasts and hematopoietic stem cells (57,58). Those studies also reported changes in the overall size of the cells or the whole animal as well as in the growth of cells (49,57,58). However, we did not see any difference in basal Rac GTP levels among bcr Ϫ/Ϫ , abr Ϫ/Ϫ , and (abr ϫ bcr) Ϫ/Ϫ BMMs, nor did we observe any change in the overall cell size of BMMs or the whole animal (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced PTEN activity may contribute to the protective effect of ROCK inhibition in endothelial cells [148] and to the protective effects of suppression of ROCK1 in cardiomyocytes [13]. In addition, ROCK has been shown to interact with and negatively regulate insulin receptor substrate 1 (IRS1) signaling and PI3-kinase activation in vascular smooth muscle cells [9] and in fibroblasts derived from p190B RhoGAP null mice [131]. In contrast, a recent study has shown that ROCK interacts with and phosphorylates IRS1 at Ser632/635 sites thereby enhancing PI3-kinase activation in adipocytes and muscle cell lines and in isolated soleus muscle ex vivo [39].…”
Section: Substrates Of Rockmentioning
confidence: 99%